Islamic financial system and conventional banking: A comparison - Asma Salman; Huma Nawaz (Arab Economic and Business Journal, 2018)
The present study is conducted to find out the difference between the two areas of banking, that is, Islamic and conventional banking with respect to profitability, efficiency and liquidity. The secondary data from banks of each banking sector is taken for assessment. Ratio analysis and one sample t-test is applied to determine the characteristics of study respondents and regression analysis is applied to examine the difference in term of significant factors that influence customer trust of Islamic banks and commercial banks. The results of the study oppose many previous findings as the analysis shows that there is significant difference between the both types of banking for the variables under study. Moreover, influence of return on asset is more on customer trust for the study period (2013-2017) for the Islamic bank as compared to the conventional banking. The study also examines the significant factors that are important for growth of Islamic banking.
Keywords: 330; Islamic banking; Profitability; Efficiency; Liquidity